Faktor - Faktor Yang Mempengaruhi Penerimaan Pengguna Terhadap Layanan E-SPTPD Di Kota Surakarta - Debby Yohana Pandey; Rino Ardhian Nugroho (Publica: Jurnal Pemikiran Administrasi Negara, 2020)
At this time the growth of information technology very quick which has significant impact on human life. This encourage changes in various sectors of people life along with the development of information and Comunication of Technology (ICT). Even the Government which utilizes information technology system, namely Electronic Government. The city of Surakarta, especially BPPKAD Surakarta has to begun to implement e-Government in the area of local tax services, one of which is E-SPTPD or Electronic Regional Tax Return to facilitate report and payment of local taxes. However, the successful use of e-Government is not accompanied by success at the user level. Therefore, this study will determine the factors that affect the acceptance of E-SPTPD service users in Surakarta. This study uses Unified Model of Electronic Government (UMEGA). This research was conducted by distributing questionnaires with a total sample of 74 local taxpayers in the city of Surakarta. Data analysis using the Structural Equation Model (SEM-PLS) with the Smart PLS 3 application. The results of this study indicate that the factors that influence E-SPTPD service users are performance expectation, social influence, user attitudes. When the level of use and interest of service users, especially local taxpayers, increases, it will increase the compliance of local taxpayers to be able to report and pay taxes in a timely manner. So that this compliance will increase local tax revenue.